Moderating Effect of Sex, Age, and Education on the Relationship between Death Attitude and Aspiration of Life - Karki, Tej Bahadur; Khadka, Kalpana; Manandhar, Dev Chandra (International Journal of Atharva, 2026)
Background: Attitudes toward death significantly influence how individuals plan and pursue life goals, yet the relationship between death attitudes and life aspirations remains underexplored among Nepalese youth, a population navigating rapid social change and significant mental health challenges.Objectives: This study aimed to examine the relationship between death attitudes (including death anxiety, avoidance, and acceptance) and life aspirations among Nepalese youth, and to investigate the moderating roles of sex, age, and education in this relationship.Methods: A quantitative, correlational research design was employed with a sample of 391 youth from the Kathmandu Valley, selected through simple random sampling. Data were collected using the Death Attitude Profile–Revised (DAP-R) and the Aspiration Index. Correlation and regression analyses were conducted to assess associations and moderating effects.Findings: A statistically significant positive correlation was found between death attitude and life aspiration (r = 0.328, p < .01), indicating that more adaptive attitudes toward death are associated with higher life aspirations. Moderation analyses revealed that sex and education significantly moderated this relationship, while age did not. The interaction effects for sex (β = 0.171–0.183) and education (β = 0.145–0.164) were consistent across positive, negative, and total death attitude models.Conclusion: The findings demonstrate that death attitudes are meaningfully associated with the life aspirations of Nepalese youth, with this relationship being stronger for females and those with higher education. This suggests that death attitudes can serve as catalysts for goal formation rather than solely as sources of distress.Novelty: This study is among the first to empirically establish the link between multidimensional death attitudes and life aspirations in the Nepalese context, identifying sex and education as critical moderators, thereby providing a foundation for culturally relevant theory and intervention development.